HUBUNGAN ANTARA RUTINITAS SHALAT DHUHA DENGAN HASIL SKRINING OSTEO ARTHRITIS PADA LANSIA MUSLIMAH - KAISAR BALEMUN HARAHAP; ELMAN BOY (LP2MTBM MAKARIOZ, 2021)
Osteo Arthritis (OA) is a disease that is often found in the elderly which attacks joints and is chronic in nature, which has thecharacteristics of pain in the knee joint, stiffness, limited movement, crepitus, muscle weakness, and deformity of the kneejoint. Diagnosis of OA can only be done by imaging examination, which is a radiological examination that is interpreted usingthe Kellgren-Lawrence scale, so that it can be distinguished based on joint space narrowing. Initial screening for this diseasecan use the Western Ontario and McMaster University Osteoarthritis Index (WOMAC) questionnaire, so that it can bedistinguished between the population that needs to be tested by the gold standard to confirm the state of OA in thesepatients. The purpose of this study was to determine the relationship between the routine of praying dhuha and the results ofosteoarthritis screening in elderly Muslim women. This study is a descriptive-analytic study with a cross-sectional design.The subjects of this study were elderly Muslim women with a total of 30 people. This study uses data collection techniqueswith total sampling with the Spearman test. Collecting data by filling out a questionnaire. This study shows that there is asignificant relationship between the variables of Western Ontario and McMaster University Osteo Arthritis Index and DhuhaPrayers as evidenced by a p value of 0.000 (p <0.05) with a correlation coefficient value of 0.627. There is a relationshipbetween Western Ontario and McMaster University Osteo Arthritis Index and Dhuha Prayers.